A cross‐sectional study examining the prevalence of antibiotic‐resistant Cutibacterium acnes isolated from patients with acne in Bangkok, Thailand - Peerada Sermswan; Rakwaree Sriharat; Supichcha Saithong; Matchima Laowansiri; Nutchaya Amornruk; Direkrit Chiewchengchol; Nopadon Noppakun; Pravit Asawanonda; Tanittha Chatsuwan; Chanat Kumtornrut (The Journal of Dermatology, 2023)
= 0.3). The present prevalence of antibiotic-resistant C. acnes was high in Thailand. Antibiotic stewardship in AV treatment should be encouraged to prevent further antibiotic resistance crises.
Keywords: Acne and Rosacea Treatments and Effects; Dermatology and Skin Diseases; Dermatological diseases and infestations